Education on Organic Waste Management as an Effort in Emergency Waste Mitigation Communication: Edukasi Pengelolaan Sampah Organik Sebagai Upaya Komunikasi Mitigasi Darurat Sampah - Ardianti, Dhini Ardianti; Affandi, Nur Ratih Devi Affandi; Wifka, Wifka R.Syauki; Rasid , Muhammad Rasid AE; Fauzi, Rahman Fauzi (Institut Riset dan Publikasi Indonesia, 2024)
The Community Partnership Program (PKM) education on organic waste management as an effort to communicate waste emergency mitigation. The partner is SMAN 1 Margaasih Bandung Regency, which has a total of around 1,080 students plus school personnel, including leaders, teachers, education staff, and school canteen traders, all of whom produce a significant amount of waste daily. The issue faced by the partners is their lack of awareness about the waste emergency in Bandung Raya (include Bandung Regency), as well as their lack of understanding regarding waste sorting and the various methods of handling different types of waste. The problem-solving approach with Generation Z involves the PKM team's KIE outreach on emergency waste mitigation, interactive games, and waste sorting simulations according to different waste types, as well as facilitating the use of Kang Empos buckets. The method implemented includes broadcasting the outcomes achieved in this PKM activity, which are an increase in awareness and mindset about the importance of maintaining the cleanliness of the school environment, realizing the existence of a waste emergency in Bandung Raya, and starting a new lifestyle by bringing a tumbler and a container for snacks to the school canteen. This initiative aims to establish a zero-waste lifestyle, enhance soft skills (empathy and responsibility), and encourage SMAN 1 Margaasih students to create positive content or share stories on social media about waste emergency mitigation, as they see on various social media platforms.